Foot Orthosis For Patients With Diabetic Foot Ulcer - Kang, Jing Yong (Universiti Sains Malaysia, 2018)
A foot orthosis is commonly used in diabetic individuals in order to relieve pain and avoid the formation of ulcer. They can be fabricated from a variety of materials which possess different degrees of hardness, control and conformability. The research involves the comparison of five selected insole materials which are Poron_L24, Poron_L32, Nora_SLW, Nora_SL and Nora_AL for the three-dimensional (3D) finite element (FE) analysis of the three foot models, the determination of the effect of peak plantar pressure with the presence of ulcer, and the investigation whether FE analysis of a 3D Computational Aided Design (CAD) model of human foot generated from a 3D scanner can be used to predict the plantar pressure distribution of a diabetic foot ulcer. All of this studies were done using ANSYS 16.0. Meanwhile, the 3D foot model for the FE analysis was obtained by using a 3D scanner after preparing a human foot sample. From the FE analysis, Poron_L24 was determined to be the most effective material in reducing the peak plantar pressure for all three foot models (15.96% for the healthy foot model, 29.82% for the foot model with an ulcer at 1st metatarsal region and 33.17% for the foot model with an ulcer at heel region). Hence, it showed that a softer and open cell foam insole material able to reduce the most peak plantar pressure of the foot. Besides, the FE analysis also showed that the presence of ulcer causes the peak plantar pressure of the foot to drastically increase up to approaching 40%. A foot with an ulcer at metatarsal region was found to have increase the peak plantar pressure by 38.8% while a foot with an ulcer at heel region was found to have increase the peak plantar pressure by 38.6%. Furthermore, the FE analysis of a 3D CAD model of a human foot was proven to be able to predict the plantar pressure distribution of a diabetic foot ulcer as the percentage deviation of peak plantar pressure from previous works is below 10% (4.3% for Cheung and 7.6 % for Tao) and had a percentage difference up to 5% when it was compared with the method used by Cheung.